Default and devaluation risks in Argentina: long-run and exogeneity in different systems - Ahumada, Hildegart (2000)
This study analyses the effect of devaluation risk on the default risk of Argentina, a critical question for the “dollarization debate”. The integrated nature of both series is taken into account to analyse the long run relationship and to evaluate “weak exogeneity” using a “cointegrating vector” system approach. First a bivariate system is considered and then the default risk in the region and indicators of macroeconomic performance are included. The results show that only devaluation risk adjusts to reach the equilibrium with the default risk. Once this risk is free from the effect of Latin American default risk, the solvency of the government (measured as the ratio of government debt to GDP) is the only factor that can be detected in the long run. Conclusions about weak exogeneity do not change when the information set is expanded.